SCREENING FOR MAIZE RESISTANT GENOTYPES AGAINST STALK BORERS’ (Sesamia calamistis Hampson) INFESTATION IN MINNA, NIGER STATE, NIGERIA - Idowu, G.A.; Oyewale, R.O.; Jiboh, B.S.; Bolajoko, M.H.; Ibrahim, H.M.; Bello, A.K (Big Data in Agriculture)
The experiment was conducted at the screenhouse of the Department of Crop production, Federal University of Technology Minna, (Gidan Kwano Campus) Niger state. The maize genotypes were obtained from the International Institution of Tropical Agriculture (IITA) Ibadan, Oyo state while the stem borer larvae were reared at the Department of Crop Protection, Faculty of Agriculture, Ahmadu Bello University Zaria, Kaduna state. Average infested plants were converted to percentage infestation. Analysis of variance (ANOVA) was carried out using Minitab Package and the significant means were separated using Duncan Multiple Range Test (DMRT). The result revealed that maize genotypes under stem borer infestation showed significant variations in plant height and stem diameter at various weeks under study. Result also showed significant variation among genotypes for yield parameters although number of days to silking showed no variation among treatments. MG-J had the least significant number of days to tasseling, MG-A recorded the highest number of ears followed by MG-S. It was concluded that MG-H and MG-S had the lowest rate of infestation. MG-C and MG-A had the highest grain yields among the genotypes. Therefore, MG-H and MG-S were recommended as tolerant maize genotypes while MG-C and MG-S were also recommended as high yielding maize genotypes among other genotypes under study.